Significance of the localization of phosphorus among tissues on a cross-section of leaf lamina of Bornean tree species for phosphorus-use efficiency - Tsujii, Yuki; Oikawa, Masakazu; Kitayama, Kanehiro (Journal of tropical ecology, 2017)
A greater relative allocation of phosphorus (P) to photosynthetically active cells functions to maintain a rapid photosynthesis under P limitation, and may be a key mechanism of plants to use P efficiently. This mechanism has not been studied in tropical trees despite the productivity of tropical forests often being limited by P. In this study, the spatial distribution of P among tissues on a cross-section of leaf lamina was analysed for 13 tree species from P-limited sites on Mount Kinabalu, Borneo. Most species showed greater P concentration in palisade mesophyll than in spongy mesophyll and epidermal tissues, suggesting that tropical trees under P limitation localize foliar P in photosynthetic palisade mesophyll.